THE DIFFICULTIES AND CONFACES OF THE CURRENT SCHOOL SYSTEM IN FACE WITH THE CONSTANT DANGER OF DRUGS AND EXTERNAL VIOLENCE - de Souza Cazaes, Gilson (Revista Gênero e Interdisciplinaridade, 2023)
This article has, as an important and necessary backdrop, the regrettable and extremely worrying situation that has been occurring in the current school system. A recurring situation in several school units, which in addition to dealing with old problems, both structural and pedagogical, without forgetting to mention issues linked to professional development, has been added to these the serious reality of drugs. The spread and use of prohibited substances among school-age teenagers has, unfortunately, become increasingly common; and this research instrument and scientific approach seeks to offer elements that will contribute to positive initiatives, in the face of the serious challenges that the new and delicate social reality imposes on the needy and fragile Brazilian educational system. Using important approaches from renowned theorists and researchers, the research written here seeks to substantiate its simple argument, knowing that in the case of a delicate topic that has destructive and disintegrating potential for lives and families, we do not fail to understand that we do not bring a formula magic for such a delicate topic. What is proposed and, as said, is to make a small contribution in the face of an immense ocean of challenges and difficulties such that they can tie the hands of the Public Power with all its apparatus. Finally, the references adopted, when applied and inserted into the structure of this article, managed, even without claiming to be exhaustive, to make its presentation less evasive and redundant.